The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s10620-007-9982-2
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Activating Factor (PAF) Antagonism with Ginkgolide B Protects the Liver Against Acute Injury. Importance of Controlling the Receptor of PAF

Abstract: Platelet activating factor (PAF) is an ubiquitous phospholipid that acts as a mediator of numerous pathophysiological conditions, including hepatotoxicity. The present study has been conducted to evaluate the eventual role of the platelet activating factor in post-acetaminophen intoxication of liver, using ginkgolide B, BN52021, a selective PAF receptor antagonist. One group of rats was treated with a toxic dose of acetaminophen (APAP) (3.5 g/kg b.w.) (control group) and a second one with the same dose of APAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 52 publications
0
18
0
1
Order By: Relevance
“…In addition, ginkgolide B has many other biological functions. For example, ginkgolide B can specifically inhibit effects of platelet activating factor (PAF) via competitively binding to PAF receptor [25]. In our study, we demonstrated that ginkgolide B effectively inhibited EFV-induced ROS production and endothelial permeability.…”
Section: Discussionmentioning
confidence: 54%
“…In addition, ginkgolide B has many other biological functions. For example, ginkgolide B can specifically inhibit effects of platelet activating factor (PAF) via competitively binding to PAF receptor [25]. In our study, we demonstrated that ginkgolide B effectively inhibited EFV-induced ROS production and endothelial permeability.…”
Section: Discussionmentioning
confidence: 54%
“…; Grypioti et al. ). Ginkgo biloba is a PAF receptor antagonist that is excreted unchanged in the urine (Braquet ; Becker et al.…”
Section: Discussionmentioning
confidence: 97%
“…; Grypioti et al. ). Extracted from Ginkgo biloba, ginkgolide B is excreted unchanged in the urine making it an ideal therapeutic intervention for managing bladder inflammation (Kimbel ).…”
Section: Discussionmentioning
confidence: 97%